2023
DOI: 10.3390/molecules28031270
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Discovery of Nicotinic Acetylcholine Receptor Allosteric Modulators

Abstract: Positive allosteric modulators (PAMs), negative allosteric modulators (NAMs), silent agonists, allosteric activating PAMs and neutral or silent allosteric modulators are compounds capable of modulating the nicotinic receptor by interacting at allosteric modulatory sites distinct from the orthosteric sites. This survey is focused on the compounds that have been shown or have been designed to interact with nicotinic receptors as allosteric modulators of different subtypes, mainly α7 and α4β2. Minimal chemical ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 131 publications
0
13
0
Order By: Relevance
“…44,46−48 The high-nanomolar/low-micromolar IC 50 values exhibited by 8j, 9c, and 9j as heteromeric nAChR NAMs are comparable to the antagonist potencies of small-molecule reference antagonists in this field, 3,49 and this new NAM class certainly complements the very few NAMs presently identified in the nAChR field. 22,23,28 Although the therapeutic potential in nAChRs historically primarily has been pursued through development of agonists and PAMs, nAChR inhibition through competitive antagonists or NAMs has also been proposed to hold perspectives for various psychiatric indications. 50−52 In support of this, the non-selective nAChR channel blocker (S)-(+)-mecamylamine has reached phase III clinical trials for depression and other psychiatric disorders, 53 and the α7selective NAM BNC210, another indole-based allosteric nAChR modulator (Figure 1), recently entered clinical trials for anxiety disorders.…”
Section: ■ Discussion and Conclusionmentioning
confidence: 99%
“…44,46−48 The high-nanomolar/low-micromolar IC 50 values exhibited by 8j, 9c, and 9j as heteromeric nAChR NAMs are comparable to the antagonist potencies of small-molecule reference antagonists in this field, 3,49 and this new NAM class certainly complements the very few NAMs presently identified in the nAChR field. 22,23,28 Although the therapeutic potential in nAChRs historically primarily has been pursued through development of agonists and PAMs, nAChR inhibition through competitive antagonists or NAMs has also been proposed to hold perspectives for various psychiatric indications. 50−52 In support of this, the non-selective nAChR channel blocker (S)-(+)-mecamylamine has reached phase III clinical trials for depression and other psychiatric disorders, 53 and the α7selective NAM BNC210, another indole-based allosteric nAChR modulator (Figure 1), recently entered clinical trials for anxiety disorders.…”
Section: ■ Discussion and Conclusionmentioning
confidence: 99%
“…The uncorrected melting point of DM506 was measured using a SMP3 apparatus (Stuart-BioCote, Staffordshire, UK). 1 H NMR and 13 C NMR spectra were recorded using a Bruker NMR 400 AVANCE spectrophotometer (Faelladen, Switzerland). DM506 (base and fumarate salt) samples were dissolved in CDCl 3 and CD 3 OD, respectively, and placed in 5 mm NMR tubes.…”
Section: Chemical Characterizationmentioning
confidence: 99%
“…Pharmacological studies showed that tabernanthalog and ibogainalog act, depending on the receptor subtype, as agonists or antagonists at a variety of metabotropic serotonin receptors . However, there was only one result (extended data), indicating that 10 μM tabernanthalog slightly inhibited (<20%) the α3β4 nicotinic acetylcholine receptor (nAChR), which is considered an important target for the antiaddictive activity of coronaridine congeners. , Considering that nAChRs are involved in many pathological conditions, including depression, anxiety, addiction, chronic pain, and cognitive impairments, ,,, we investigated the pharmacological profile of DM506 at different nAChRs representing the predominant subtypes expressed in the nervous system. To determine the mechanisms of inhibition, voltage-dependence and functional competition experiments as well as molecular docking and molecular dynamics (MD) simulations were performed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations